Modernization as a Means of Improving Financial and Economic Adaptability Hotel Business - Lomova, Lyudmila A.; Mamycheva, Diana I.; Rovovaya, Tatyana A.; Romanova, Irina A.; Nekrasova, Marina L.; Anisimova, Victoria V. (International Review of Management and Marketing, 2016)
The strategic goal of the modernization of the hotel business is to ensure its adaptability in a rapidly changing and unexpected external and internal environment. The position of the hotel enterprise may become unstable, or adaptive because of internal production and technological problems, failures in the supply chain, disorders of the information and communication systems, changes in consumer demand, increased activity of competitors. Achieving strategic stability hotel enterprise depends on the achievement of two main components: security (reducing the likelihood of failures in the various subsystems of the enterprise) and increase adaptability (development of the ability to restore the key performance indicators). The basis of improving the safety operation of the hotel enterprise is to create a system of protection against failures based on prediction, early detection and elimination of negative situations. Such a system should provide for the mandatory inclusion of all personnel in the work of security companies, as well as cooperation with partners, bodies of state and municipal government and even competitors. Keywords: hotel business, modernization, customer demand, competitor activity JEL Classifications: L21; P48